Rehabilitation and conservation framework of old inner area in Asian Mega Cities - Teh, Yee Sing; Sasaki, Yoh (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
This paper addresses the framework of rehabilitation and conservation of old inner city areas in Asia which have so far received very little attention in urban development process. To ensure these areas are dynamic and evolving over time, exploring the heritage conservation concepts and urban planning idea in term of conservation values and honoring it into the principles and elements through the urban planning process not only help the new urban infrastructures greatly, but also cause the urban sustain the development in historic contexts and its identity. Thus, the need for urban rehabilitation and conservation is discussed with reference to a number of cases, i.e., Tokyo, Shanghai, Hanoi, and Penang. The method and system which have been implemented during the process of conserving the old inner city would be reviewed. From the particular models, delineation of the framework is provided, and some key aspects of rehabilitation and conservation are highlighted. The paper concludes with considerations on the value for area rehabilitation and revitalization approaches which contribute to tourism, cultural and socio-economic of the city. It then discussed the merit of those frameworks from the example models if they are integrated into new concepts of use in conservation effort towards the urban growth nowadays.